Síndrome HELLP com descolamento placentário e óbito fetal: relato de caso - Junior, Carlos Alberto Rodrigues; Dias, Fellipe Camargo Ferreira; Oliveira, Flávia da Silva; Sousa, Gustavo Santos; Moraes, Fábio Roberto Ruiz de; Guedes, Ana Carolina Batista de Souza (Revista de Patologia do Tocantins, 2017)
The HELLP syndrome – defined as haemolysis, elevated liver enzymes and thrombocytopenia – consists of an advanced stage of preeclampsia (PE), which can affect 0.6% of pregnancies and 4-12% of patients with severe PE. Being responsible for elevated maternal and perinatal mortality rates, it can present with general malaise, epigastralgia, right hypochondrium pain, nausea and vomits, headache, scotomas, associated with hypertension and proteinuria. Woman, 19 years old, primigest, admitted with 29 weeks of gestational age presenting with arterial hypertension (160/120 mmHg), headache, scotomas, nausea and vomits. She showed regular health status, pallid, closed, anterior and soft cervix, with no fluid losses, and inaudible fetal heart rate on the sonar. She was stabilized with intravenous hydration and antihypertensive drugs, the ultrasonography showed placental abruption and fetal death. An uneventfully caesarean operation was performed under general anaesthesia. Due to the low haemoglobin, haematocrit and platelet levels, she received blood transfusion, progressing with clinical and laboratory improvement. The pressure control was met by the use of methyldopa, nifedipine and pindolol, and she was discharged with a good health status at the 10th day of hospitalization, with scheduled return for reassessment. Keywords: HELLP syndrome, severe preeclampsia, fetal death, placental abruption. A síndrome HELLP – definida por hemólise, enzimas hepáticas elevadas e plaquetopenia – consiste em estágio avançado de pré-eclâmpsia (PE), podendo afetar 0,6% das gestações e 4-12% das pacientes com PE grave. Responsável por elevados índices de mortalidade materna e perinatal, pode se apresentar com mal estar geral, epigastralgia, dor em hipocôndrio direito, náuseas ou vômitos, cefaleia, escotomas, assoaciado a quadro hipertensivo e proteinúria. Mulher de 19 anos, primigesta, admitida com 29 semanas de idade gestacional com quadro de hipertensão arterial (160/120 mmHg), cefaleia, escotomas, náuseas e vômitos. Apresentava regular estado geral, hipocorada, colo uterino fechado, anterior, amolecido e sem perdas e batimento cardiofetal inaudível ao sonar. Estabilizada com hidratação venosa e anti-hipertensivos, foi realizada ultrassonografia que evidenciou descolamento prematuro de placenta e óbito fetal. Realizada cesariana sob anestesia geral sem intercorrências. Devido a baixos níveis de hemoglobina, hematócrito e plaquetas, foi hemotransfundida, apresentando melhora clínica e laboratorial. O controle pressórico foi atingido com uso de metildopa, nifedipina e pindolol, recebendo alta em bom estado geral no 10º dia de internação hospitalar com programação de retorno para reavaliação. Palavras-chave: Síndrome HELLP, Pré-eclâmpsia grave, óbito fetal, descolamento placentário.